The Giving Punishment of School Rules Violation in Enforcing Discipline Characters on MTs. Raudlatussa'adah Pontianak - Rianawati, Rianawati; Nurhamid, Nurhamid (Universitas Malikussaleh, 2020)
This research is motivated by the recent most cases of rule violations conducted by a number of students in MTs. Raudlatussa'adah Pontianak. From the results of observations and initial documentation of the research, the forms of violations that are often done by students are late, wearing needless uniforms, long hair, inappropriate hair cut for students, fighting and other forms of violations. Even though MTs. Raudlatussa'adah Pontianak has made written rules including the threat of sanctions / penalties for the perpetrators. Based on the background of the problem, the researcher then conducted further research in order to explore and analyze information about how the act of giving penalties in cases of school rules violations in order to uphold the character of students. The approach and method used in research is a qualitative approach with descriptive methods, that this study seeks to describe the phenomenon in accordance with the facts occurred in the field. Furthermore, the subjects in this study include: Principal of Madrasah, Deputy Head of Madrasah for Student Affairs, Teachers of Islamic Character and students. For data collection researchers used in-depth interview techniques, non-participant observation and study documentation. The data processing and analysis techniques used consist of data reduction, data presentation and conclusions. Meanwhile, to check the validity of the data, researchers used triangulation techniques. Based on the explanation and analysis of the research data, it can be concluded that the preparatory step for the punishment of school rules violations in an effort to uphold the character of student discipline is done by verbalizing the punishment in the Student Orientation Period (MOS) activities, flag ceremonies and through classroom wall magazines and billboards. . As for the implementation of the punishment given by the teacher, but it is not consistent with the existing rules and the implementation also does not contain educational elements.